Serological positive markers of hepatitis B virus in femoral venous blood or umbilical cord blood should not be evidence of in-utero infection among neonates. Issue 1 (December 2016) - Zhang, Lei; Gui, Xi-En; Wang, Bo; Fan, Jing-Yi; Cao, Qian; Mullane, Kathleen; Liang, Xiao-Li
Abstract Background Maternal-infant transmission of hepatitis B virus(HBV) occurs even after passive-active immunization. Some scholars speculate that in-utero infection may be the main cause of immunoprophylaxis failure. However, there is a lack of evidence about the possible occurrence periods of perinatal transmission. Methods From 2008 to 2012, 428 pairs of HBsAg-positive mothers and neonates were enrolled and 385 infants aged 8–12 months were followed. HBV markers (HBsAg, anti-HBs, HBeAg, anti-HBe, anti-HBc, HBV-DNA) were performed on all subjects. Results Of mothers who were positive for HBsAg, HBeAg, HBV-DNA, 35.1 %, 94.3 %, 12.7 % of their neonates were positive for those indices, respectively. Neonates' mean titers of those indices were significantly lower than their mothers'. There were no significant differences in rates of positivity and mean titers of anti-HBe and anti-HBc between neonates and mothers. Most of the positive indices turned negative during the follow-up period. Immunoprophylaxis failed in seventeen infants: four infants had HBV-DNA > 6 log10 copies/mL both at birth and in follow-up; in six infants, mean viral load was 3.72 ± 0.17 log10 copies/mLat birth and 7.62 ± 0.14 log10 copies/mL at follow-up; seven infants were HBV-DNA negative at birth but were found to have > 6 log10 copies/mL during follow-up. Infants that were immunoprophylaxis failures were all born to HBeAg-positive mothers with HBV-DNA > 6 log10 copies/mL. Conclusions The placental barrier can partly prevent maternal HBsAg, HBeAg, HBV-DNA from passing through to fetus. Performing HBsAg, HBeAg, HBV-DNA once at birth can neither diagnose nor exclude maternal-infant transmission. The diagnosis of infection period depends on the dynamic changes in viral load from birth through the follow-up period but whether the infection occurred in utero, at delivery or during the neonatal period could not be determined.